Sosialisasi Pembelajaran Matematika Dan Bahasa Inggris Untuk Anak-Anak Usia Sekolah Dasar Di Desa Janji Mauli - Nurdalilah; Adek Nilasari Harahap; Siti Meutia Sari; Tinur Rahmawati Harahap; Susi Sulastri; Mahrani (Yayasan Perguruan Kampus, 2024)
This service was conducted in response to the low motivation to learn maths and English among primary school children in Janji Mauli Village, Angkola Muaratais Sub-district. These children face difficulties in understanding maths and English materials. The purpose of this service is to assess and understand the socialisation activities of mathematics and English learning for children in Janji Mauli Village. This socialisation aims to provide assistance, advice, encouragement, and opportunities for children to be motivated in learning. The stages of coaching activities include: 1) Preparation Stage, 2) Implementation stage of socialisation. The socialisation methods used include: 1) Lecture method, 2) Question and answer method, 3) Exercise or practice method. Based on the results of this service, it can be concluded that: 1) Students' learning motivation increased, 2) Students' ability to solve maths multiplication has increased, 3) Students' ability to compose English sentences has also increased.